A 'resource allocator' for transcription based on a highly fragmented T7 RNA polymerase. Issue 7 (July 2014) - Segall‐Shapiro, Thomas H; Meyer, Adam J; Ellington, Andrew D; Sontag, Eduardo D; Voigt, Christopher A
Abstract: Synthetic genetic systems share resources with the host, including machinery for transcription and translation. Phage RNA polymerases (RNAPs) decouple transcription from the host and generate high expression. However, they can exhibit toxicity and lack accessory proteins (σ factors and activators) that enable switching between different promoters and modulation of activity. Here, we show that T7 RNAP (883 amino acids) can be divided into four fragments that have to be co‐expressed to function. The DNA‐binding loop is encoded in a C‐terminal 285‐aa 'σ fragment', and fragments with different specificity can direct the remaining 601‐aa 'core fragment' to different promoters. Using these parts, we have built a resource allocator that sets the core fragment concentration, which is then shared by multiple σ fragments. Adjusting the concentration of the core fragment sets the maximum transcriptional capacity available to a synthetic system. Further, positive and negative regulation is implemented using a 67‐aa N‐terminal 'α fragment' and a null (inactivated) σ fragment, respectively. The α fragment can be fused to recombinant proteins to make promoters responsive to their levels. These parts provide a toolbox to allocate transcriptional resources via different schemes, which we demonstrate by building a system which adjusts promoter activity to compensate for the difference in copy number of two plasmids. Synopsis: The T7 RNA polymerase is split into two to four fragments that retain activity when co‐expressed. These parts provide a toolbox to allocate resources to a genetic system, set its transcriptional activity and partition it between multiple orthogonal promoters. T7 RNA polymerase is bisected at five distinct regions and combinations of these fragments yield active three‐ and four‐piece polymerases. Specificity loop mutations introduced to the C‐terminal fragment, create variable "σ fragments" that bind to the remaining conserved "core fragment" and activate orthogonal promoters. Using the σ and core fragments, a resource allocator is built that can regulate the total transcriptional activity of a synthetic system and dynamically partition it between promoters. Further splits and mutations are used to build positive and negative regulators of the resource allocator, enabling more complex system architectures. Abstract : The T7 RNA polymerase is split into two to four fragments that retain activity when co‐expressed. These parts provide a toolbox to allocate resources to a genetic system, set its transcriptional activity and partition it between multiple orthogonal promoters.